Vasorelaxing Activity of Stilbenoid and Phenanthrene Derivatives from Brasiliorchis porphyrostele: Involvement of Smooth Muscle CaV1.2 Channels - Waratchareeyakul, Watcharee; Fusi, Fabio; Durante, Miriam; Ahmed, Amer; Knirsch, Walter; Mas-Claret, Eduard; Mulholland, Dulcie A. (Planta Medica, 2020)
Five compounds, 3,4′-dihydroxy-3′,5,5′-trimethoxydihydrostilbene, 1; 3,4′-ihydroxy-3′,5′-dimethoxydihydrostilbene, 2; 3,4′-dihydroxy-5,5′-dimethoxydihydrostilbene, 3; 9,10-dihydro-2,7-dihydroxy-4,6-dimethoxyphenanthrene, 4; and the previously unreported 1,2,6,7-tetrahydroxy-4-methoxyphenanthrene, 5 were isolated from the South American orchid, Brasiliorchis porphyrostele. An in-depth analysis of their vascular effects was performed on in vitro rat aorta rings and tail main artery myocytes. Compounds 1 – 4 were shown to possess vasorelaxant activity on rings pre-contracted by the α1 receptor agonist phenylephrine, the CaV1.2 stimulator (S)-(−)-Bay K 8644, or depolarized with high K+ concentrations. However, compound 5 was active solely on rings stimulated by 25 mM but not 60 mM K+. The spasmolytic activity of compounds 1 and 4 was significantly affected by the presence of an intact endothelium. The KATP channel blocker glibenclamide and the KV channel blocker 4-aminopyridine significantly antagonized the vasorelaxant activity of compounds 4 and 1, respectively. In patch-clamp experiments, compounds 1 – 4 inhibited Ba2+ current through CaV1.2 channels in a concentration-dependent manner, whereas neither compound 4 nor compound 1 affected K+ currents through KATP and KV channels, respectively. The present in vitro, comprehensive study demonstrates that Brasiliorchis porphyrostele may represent a source of vasoactive agents potentially useful for the development of novel antihypertensive agents that has now to be validated in vivo in animal models of hypertension.
Keywords: Brasiliorchis porphyrostele; phenanthrenes; stilbenoids; vasorelaxing; vascular CaV1.2 channel; vascular endothelium; Orchidaceae